2016
DOI: 10.1186/s12943-016-0569-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-138-5p contributes to cell proliferation and invasion by targeting Survivin in bladder cancer cells

Abstract: BackgroundSurvivin (encoded by the gene BIRC5) plays an important role in the carcinogenesis of bladder cancer. Identifying miRNAs that target Survivin in the setting of bladder cancer will help to develop Survivin-based therapies for bladder cancer.MethodsThe expression levels of miR-138-5p and Survivin protein were measured in 12 resected bladder cancer specimens. The correlation between miR-138-5p and Survivin was further examined by evaluating Survivin expression in human bladder cancer cell lines that eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…On the other hand, survivin is an oncogene that regulates the apoptosis, proliferation, and invasion of many cancers [25][26][27]. Knockdown of survivin by using siRNA could dramatically suppress the proliferation and invasion of bladder cancer cells [8]. Co-silencing of Livin and Survivin can effectively inhibit the cell proliferation and apoptosis of lung cancer cells [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, survivin is an oncogene that regulates the apoptosis, proliferation, and invasion of many cancers [25][26][27]. Knockdown of survivin by using siRNA could dramatically suppress the proliferation and invasion of bladder cancer cells [8]. Co-silencing of Livin and Survivin can effectively inhibit the cell proliferation and apoptosis of lung cancer cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Survivin expression is minimal in normal tissues; therefore, it has become a lead target for both as a tumor diagnostic, prognostic and for anti-cancer therapies. Mounting evidence has demonstrated that survivin takes part in the regulation of cell cycle, apoptosis, cell proliferation as well as invasion and play important roles in various tumor carcinogenesis, such as gastric cancer [7], bladder cancer [8], epithelial ovarian cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported that there are many miRNAs that play a part in regulating the progression of cancer. Yang et al (19) reported that miR-138-5p is a tumor suppressor that inhibits cell proliferation and invasion by targeting Survivin. In prostate cancer, papillary thyroid carcinoma, and head and neck carcinoma, both miR-26a-5p and miR-26b-5p could inhibit tumor progression (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the downregulation of miR-138-5p plays an important role in various cancers. For example, it was reported that miR-138-5p could inhibit BIRC5 translation and suppress the BIRC5-meditated carcinogenesis of bladder cancer [45]. Similarly, miR-138-5p was also downregulated in human colorectal cancer (CRC) and dramatically promoted CRC cell growth and tumorigenesis by targeting PD-L1 [46].…”
Section: Discussionmentioning
confidence: 99%